Pengembangan Media Pembelajaran Augmented Reality untuk Materi Sistem Pencernaan Manusia - Karentius, Maret Rista; Hardiyantari, Oktavia (Universitas Negeri Gorontalo, 2025)
The rapid development of information technology, particularly in mobile devices, has opened new opportunities for educational innovation. This study aims to develop Augmented Reality (AR)-based learning media for eighth-grade junior high school students on the topic of the human digestive system. The research employed a Research and Development (RD) methodology using the Multimedia Development Life Cycle (MDLC) model, which includes the stages of concept, design, material collecting, assembly, testing, and distribution. The resulting application features interactive elements, including quizzes and 3D Augmented Reality visualizations of digestive organs to enhance students' understanding of complex concepts. Feasibility testing involved assessments by media experts, material experts, and students, achieving feasibility percentages of 75%, 91%, and 89%, respectively, classifying the media as